Pengembangan Media Putar Tata Surya Untuk Pembelajaran IPA Siswa Kelas VI Sekolah Dasar - Amalia, Iis; Septiana, Devi; Desmiati, Indry; Rachmah, Nisrina Ainur (Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This study focused on creating an innovative learning tool – a rotating solar system model – to help sixth-grade elementary students in Natural Sciences (IPA) better understand the solar system. We identified key challenges in teaching this topic: students often showed low interest and struggled with the abstract concepts of planetary movement. To address these issues, we used a Research and Development (R&D) approach following the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The rotating solar system model was designed as a three-dimensional teaching aid that students could manually rotate. This simple yet educational design visually demonstrates the orbit and rotation of planets around the sun. During development, we consulted with subject matter experts and media experts to ensure the content's accuracy and visual quality. Validation results were highly positive, with average scores of 88% from subject experts, 83% from media experts, and 92% from practitioners, all categorized as